Jawabanmu

Jawaban paling cerdas!
2014-06-30T22:30:35+07:00
Sinx - Cosx = 1/5
(Sinx - Cosx)² = (1/5)²
Sin²x + Cos²x - 2SinxCosx = 1/25
         1           -  2SinxCosx = 1/25
2SinxCosx = 25/25 - 1/25 = 24/25
SinxCosx = 12/25 ⇔ (SinxCosx)² = (12/25)² ⇔ Sin²xCos²x = 144/625

Sin^6x+Cos^6x = (Sin²x+Cos²x)³ - 3Sin²xCos²x(Sin²x + Cos²x)
                       = (1)³ - 3(144/625)(1)
                       = 1 - 432/625
                       = 625 - 432
                               625
                       = 193/625
2 5 2